The Impact of World Crude Oil Price Changes on the Malaysian Economy: an Input-Output Analysis - Mohd Khairul Hisyam, Hassan; Senarita Tarang, Jenggie (Malaysian Economic Association, 2012)
By using Input-Output(I-O)and multipliers analysis, this paper intends to measure the impact of tourist's expenditure in Malaysian economy. The importance of impact is described by multipliers, the total refers to the multipliers of output, income, and employment. By knowing the multipliers, the total economics impact generated by the tourist's expenditure can be computed. The result indicate manufacturing and finance, insurance real estate and business service sectors are the main contributors to the Malaysian economy output, particularly in boosting the tourism sector's output. In conclusion, since this industry showing its capability in contributing towards generating the Malaysian economy growth, the policy makers should provide the appropriate policy recommendations for future economics development strategy in tourism industry by identifying the key sectors that interrelated with tourism.